Medical Dispute Resolution by Using Peace Principles - Juli, Cep; Fakhirah, Efa Laela; Afriana, Anita (Dinasti Research, 2025)
The national development program in the health sector seeks to improve the level of public health. In an effort to realize the goals of national health development, the medical profession is a noble profession that is the main pillar. The provision of health services involves doctors and patients who are legal subjects involved in the field of health care and create medical and legal relationships. This relationship can cause conflict in its implementation. Lack of good communication and unsatisfactory quality of information from doctors to patients are the main triggers of conflict. In general, disputes in the health sector are resolved through the judicial system, which tends to cause disputes. Alternative dispute resolution is an approach to resolving conflicts amicably, without involving the courts. The most important and effective form of this approach is mediation. The advantage of using mediation is that the procedure is simple, effective, speeds up the process of resolving cases, lowers costs, provides an opportunity to achieve resolution of problems by agreement, and The decision is still under the control of the parties to the dispute. Mediation contributes to the maintenance of healthy relationships between the involved individuals or groups by ensuring their dedication to the mediation outcome and providing legal options in case of non-fulfillment